DARI KOTA MANCANEGARA TIMUR HINGGA GEMEENTE: PERKEMBANGAN KOTA PASCA PEMBERLAKUKAN UU DESENTRALISASI 1903 - Hudiyanto, Reza (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2020)
Modernization pioneered by Marshaal Daendels in 1808 has reach its peak in 1903.  The old centralized government system of has been dismantled and replaced by a new modern institution one. The power of Regent reduced extremely. Part of his power was took over by Major, as a head od a new body of Government who administered the city.  The new wave also occurred in a middle-sized city of Madiun. Located in hinterland of Java, the government and people living inside must adapt tonew modern city administration. This article tried to describe the impact of new system, and problem faced by government on those process from 1918  to 1941. In order to find this answer, this research is conducted by historical methods. Finding, appreciating, interpreting information and presenting are the four steps in this method. From the research, it can be concludes that this regulation raised many problems. Profit share between City Government and Construction Corporation, shows the problem in financial matter. The local budget indicates that municipal city of Madiun are still strongly depend on capital flows from Batavia. The plan of self-financing local government is not making sense since most indigenous people reluctant to pay retribution or new tax as the consequences of new Municipal system. Even so, financial support from Central Government pave the way for Madiun in modernizing the infrastructure such as new roads, good and clean central market, strict control on flesh traffic, drainage system, street lighting, fire brigade, watering and cleaning service and city water plants. Otherwise, decentralization play important role in making modern landscape for colonial city in interior Java. It also providing fields of political training for many prominent indigenous elites.